Pengaruh Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur yang Terdaftar Di BEI - Putri Mirinda Dwi Damayanti; Ratna Septiyanti (Goodwood Publishing, 2022)
This study aims to examine the disclosure of corporate social responsibility, the effect of good corporate governance mechanisms and company size on the company's financial performance which is reflected in the return on assets (ROA). This study used a sample selection method which was carried out using a purposive sampling method, namely by selecting a sample based on certain criteria as desired by the researcher. Based on the sample selection method, 124 samples were obtained consisting of 34 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 4 periods, namely 2016 to 2019. The analytical method used in this study was a quantitative method, with classical assumption tests and analysis. multiple linear regression. The results of this study indicate that Corporate Social Responsibility has a positive effect on financial performance. This shows that the higher the level of Corporate Social Responsibility, the higher the financial performance. Good Corporate Governance has a positive effect on financial performance. This shows that the higher the Good Corporate Governance, the better the performance. Firm size has a positive effect on financial performance. This shows that the higher the size of the company owned, the better the financial performance.